2019
DOI: 10.1039/c9cc04517a
|View full text |Cite
|
Sign up to set email alerts
|

Selective RNA interference and gene silencing using reactive oxygen species-responsive lipid nanoparticles

Abstract: The integration of reactive oxygen species (ROS)-responsive thioketal group into lipids nanoparticles enables the efficient delivery of siRNA into cells, and selectively cancer cell gene expression silencing in response to the high level of intracellular ROS in cancer cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 33 publications
0
27
0
Order By: Relevance
“…The siRNAs were transfected using Interferin (Polyplus #409) at a final concentration of 30 nM. Two siRNA couples, siTRIM47 #1 and #2 targeting human TRIM47 were used 34 and a non-specific siRNA as negative control (Eurogentec ® ). SiRNA-depletion was then resolved by sodium dodecyl sulphate–polyacrylamide gel electrophoresis using TRIM47 antibody (Thermofisher Scientific, #PA5-50892).…”
Section: Methodsmentioning
confidence: 99%
“…The siRNAs were transfected using Interferin (Polyplus #409) at a final concentration of 30 nM. Two siRNA couples, siTRIM47 #1 and #2 targeting human TRIM47 were used 34 and a non-specific siRNA as negative control (Eurogentec ® ). SiRNA-depletion was then resolved by sodium dodecyl sulphate–polyacrylamide gel electrophoresis using TRIM47 antibody (Thermofisher Scientific, #PA5-50892).…”
Section: Methodsmentioning
confidence: 99%
“…9,32 More recently, we demonstrated that integrating reactive oxygen species (ROS)-cleavable thioketal moiety into lipid nanoparticles promotes intracellular lipid degradation and cargo release in cancer cells for an enhanced gene silencing. 33 We hypothesized that such a ROS-enhanced delivery strategy could be similarly adapted for delivering RNase A-QPN to promote protein release inside cancer cells, enabling NQO1-catalyzed RNase A-QPN activation. Thus, we synthesized a library containing 12 ROS-responsive lipids (Figure S6) via the Michael addition between aliphatic amine and acrylate (Scheme S2, Supporting Information).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…However, the conditional control of RNase A-QPN activity by tumor-cell-specific NQO1 is greatly prevented by the low efficiency of the protein in entering the cells. It is therefore of utmost importance to deliver the protein conjugate into tumor cells to enable NQO1 activation and targeted cancer therapy. Recently, we used a combinatorial strategy to synthesize a library of cationic lipids, and to screen effective protein delivery vehicles by self-assembling protein–lipid nanoparticles. , More recently, we demonstrated that integrating reactive oxygen species (ROS)-cleavable thioketal moiety into lipid nanoparticles promotes intracellular lipid degradation and cargo release in cancer cells for an enhanced gene silencing . We hypothesized that such a ROS-enhanced delivery strategy could be similarly adapted for delivering RNase A-QPN to promote protein release inside cancer cells, enabling NQO1-catalyzed RNase A-QPN activation.…”
Section: Results and Discussionmentioning
confidence: 99%
“…[33][34][35][36][37] Herein, we used a cationic lipid, EC16-80, which had recently been developed for effective protein delivery. EC16-80 was screened from a combinatorial library of lipid nanoparticles, 23,38,39 for simultaneous delivery of RNase A-NBC and β-Lap into cells (Figure 1b). In the lipid nanoparticle formulation, RNase A-NBC was encapsulated mainly via electrostatic interaction with EC16-80, whereas β-Lap was entrapped in the hydrophobic layer of the lipid nanoparticles (Figure 1b).…”
Section: Enzymatic Activation Of Rnase A-nbc In Living Cellsmentioning
confidence: 99%